2005
DOI: 10.1002/pbc.20616
|View full text |Cite
|
Sign up to set email alerts
|

Urinary hepcidin in congenital chronic anemias

Abstract: This study examines hepcidin levels in congenital anemias. In SCA, hepcidin was suppressed and inversely associated with erythropoietic drive. In thalassemic syndromes, hepcidin was suppressed relative to the degree of iron burden. Transfusion led to increased uhepcidin. In thalassemia, the relative influence of known hepcidin modifiers was more difficult to assess. In thalassemic syndromes where iron overload and anemia have opposing effects, the increased erythropoietic drive may positively influence hepcidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
119
3
13

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 156 publications
(146 citation statements)
references
References 16 publications
10
119
3
13
Order By: Relevance
“…Previous studies have indicated that suppression of hepcidin is greater in patients with thalassemia intermedia than TM, 14 suggesting that by suppressing erythropoiesis, transfusion permits hepcidin levels to increase 12,13 ; this effect occurs dynamically across the transfusion cycle in patients with TM. 16 However, in our population, hepcidin concentrations were similarly suppressed in patients with both severe and moderate clinical phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that suppression of hepcidin is greater in patients with thalassemia intermedia than TM, 14 suggesting that by suppressing erythropoiesis, transfusion permits hepcidin levels to increase 12,13 ; this effect occurs dynamically across the transfusion cycle in patients with TM. 16 However, in our population, hepcidin concentrations were similarly suppressed in patients with both severe and moderate clinical phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Iron from transfusions compounds iron loading. Hepcidin concentrations are suppressed in b-thalassemia, 11,12 as is hepatic HAMP mRNA expression in patients with thalassemia major (TM) 13,14 and in the C57Bl/6 Hbb th3/1 thalassemia mouse model. 15 However, patients with thalassemia intermedia exhibit lower liver HAMP mRNA than those with TM, 14 probably because of the transfusions that are required to stabilize TM disease.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In contrast to human patients who have dramatically reduced hepcidin production even in adulthood, [2][3][4][5] in the Th3/1 model, liver hepcidin mRNA expression is only low in young mice compared with wild-type (WT) mice of the same age; in adult Th3/1 mice, hepcidin expression becomes similar to that of WT mice. 10,11 However, even in adult Th3/1 mice, hepcidin levels are inappropriately low, considering their iron overload, consistent with the concept that inadequate levels of hepcidin cause the iron overload in thalassemic mice.…”
Section: Introductionmentioning
confidence: 99%
“…1 In b-thalassemia intermedia, patients do not require regular blood transfusions. 1 Even without the added iron load of transfusions, pathological suppression of the iron-regulatory hormone hepcidin [2][3][4][5] in patients with b-thalassemia syndromes results in excessive iron absorption. Subsequent iron accumulation in the liver, endocrine glands, and other organs leads to oxidative damage and severe clinical complications predominantly involving hepatic, endocrine, and vascular systems, but sparing the heart, at least compared with transfused patients.…”
Section: Introductionmentioning
confidence: 99%
“…If hepcidin synthesis is switched on after hemochromatosis already developed, then increased hepcidin causes redistribution of iron from parenchymal cells to macrophages, where iron is relatively nontoxic (57). In iron-loading anemias (␤-thalassemia and congenital dyserythropoietic anemia), the suppressive effect of erythropoiesis on hepcidin production (22,58) and the resulting increase in dietary iron absorption is sufficient to cause systemic iron overload and iron-mediated damage to the liver and myocardium even without blood transfusions. It remains to be seen whether exogenous hepcidin can correct the iron pathology in iron-loading anemias as well.…”
Section: Role Of Hepcidin In Iron Overload Disordersmentioning
confidence: 99%